Effects of melting, subduction-related metasomatism, and sub-solidus equilibration on the distribution of water contents in the mantle beneath the Rio Grande Rift. (1st December 2019) - Schaffer, Lillian A.; Peslier, Anne H.; Brandon, Alan D.; Bizimis, Michael; Gibler, Robert; Norman, Marc; Harvey, Jason
Abstract: The distribution of water in the upper mantle plays a crucial role in the Earth's deep water cycle, magmatism, and plate tectonics. To better constrain how these large-scale geochemical systems operate, peridotite and pyroxenite mantle xenoliths from Kilbourne Hole (KH) and Rio Puerco (RP) along the Rio Grande Rift (NM, USA) were analyzed for water, and major and trace element contents. These xenoliths sample a lithosphere whose composition was influenced by subduction and rifting, and can be used to examine the effects of melting, metasomatism, and sub-solidus equilibration on the behavior of water. The first result is that in KH xenoliths, olivines underwent negligible H loss during xenolith ascent, i.e. preserved their mantle water contents. These olivine water contents are used to calculate mantle viscosities of 0.5–184 · 10 21 Pa·s. These viscosity values are more than 40 times higher than those of the asthenosphere and show that KH peridotites represent samples from the lithosphere. The preservation of olivine water contents is exceptional for off-cratonic xenoliths, and the KH peridotites provide the first estimate of the average concentration of water in Phanerozoic continental mantle lithosphere at 81 ± 30 ppm H2 O. The mantle lithosphere beneath the Rio Grande rift is nevertheless heterogeneous with water contents ranging from <0.5 to 120 ppm H2 O in peridotites and from 227 to 400 ppm H2 O in pyroxenites. A composite KH xenolith of a harzburgite cross-cut by a clinopyroxenite vein shows this heterogeneity at the cm scale. The second contribution of this study stems from the majority of the KH peridotites and two of the RP peridotites having major and trace elements that can be explained by partial melting without any need to invoke metasomatic processes. This allows to show that, prior to modelling the water content variation of each peridotite mineral during melting, a correction for sub-solidus equilibration has to be applied to the water contents of the minerals. Sub-solidus equilibration also provides an explanation for the discrepancy between the clinopyroxene/orthopyroxene ratio of water contents in natural peridotites worldwide and in laboratory experiments on water partitioning in peridotite minerals. Finally, the cryptically metasomatized peridotites, rare at KH and abundant at RP, as well as the pyroxenites, permit to decipher the origin and water contents of the metasomatic melts that affected the continental lithosphere beneath the Rio Grande Rift. Trace element modelling of the metasomatized KH and RP peridotites are consistent with metasomatism via melts that are of subduction origin. Melts in equilibrium with peridotites contain more water at RP (∼1 wt.% H2 O) than at KH (∼0.5 wt.% H2 O), although this did not result in a more water-rich mantle lithosphere at RP. Rio Puerco lies within the northern Rio Grande rift, proposed to have been affected by a flat slab subduction, which may explain the more hydrous and extensive metasomatism compared to the south, where KH is located.